High third-generation cephalosporin resistant Enterobacteriaceae prevalence rate among neonatal infections in Dakar, Senegal. Issue 1 (December 2016) - Breurec, Sebastien; Bouchiat, Coralie; Sire, Jean-Marie; Moquet, Olivier; Bercion, Raymond; Cisse, Moussa; Glaser, Philippe; Ndiaye, Ousmane; Ka, Sidy; Salord, Helene; Seck, Abdoulaye; Sy, Haby; et al.
Abstract Background Neonatal infection constitutes one of Senegal's most important public health problems, with a mortality rate of 41 deaths per 1, 000 live births. Methods Between January 2007 and March 2008, 242 neonates with suspected infection were recruited at three neonatal intensive care units in three major tertiary care centers in Dakar, the capital of Senegal. Neonatal infections were confirmed by positive bacterial blood or cerebrospinal fluid culture. The microbiological pattern of neonatal infections and the antibiotic susceptibility of the isolates were characterized. In addition, the genetic basis for antibiotic resistance and the genetic background of third-generation cephalosporin-resistant (3GC-R)Enterobacteriaceae were studied. Results A bacteriological infection was confirmed in 36.4 % (88/242) of neonates: 22.7 % (30/132) during the early-onset and 52.7 % (58/110) during the late-onset periods (p  > 0.20). Group Bstreptococci accounted for 6.8 % of the 88 collected bacterial isolates, while most of them wereEnterobacteriaceae (n  = 69, 78.4 %). Of these, 55/69 (79.7 %) were 3GC-R. Thebla CTX-M-15 allele, thebla SHV and thebla TEM were highly prevalent (63.5, 65.4 and 53.8 %, respectively), usually associated withqnr genes (65.4 %). Clonally related strains of 3GC-RKlebsiella pneumoniae and 3GC-REnterobacter cloacae, the two most commonly recovered 3GC-REnterobacteriaceae (48/55), were detected at the three hospitals, underlining the role of cross-transmission in their spread. The overall case fatality rate was 18.6 %. Conclusions Measures should be taken to prevent nosocomial infections and the selection of resistant bacteria.